Pengendalian Ulatgrayak (Spodoptera litura F.) dengan Ekstrak Ubi Gadung dan Ekstrak Buah Maja - I Wayan Darmanto; Dedi Supriyatdi; Albertus Sudirman (Jurnal Agro Industri Perkebunan, 2019)
Armyworm (Spodoptera litura F.) is one of the important polyphag leaf pests that attacks almost all crops. The objective of this study was to determine the effect of various concentrations of bioinsecticide made of dioscorea tuber and aegle fruit extract on larval mortality. The research was conducted at the crop laboratory, Lampung State Polytechnic since October 2017 until December 2017. The experimental design is a completely randomized design with six treatments and four and replications. The parameters observed is mortality of armyworm larvae, which would then be analyzed using fingerprint of different varieties. That result showed that dioscorea tuber and aegle fruit extract has affected on larval mortality armyworm. Pure (100%) dioscorin tuber extract exhibited the highest larval mortality.